Ratio and difference of the cross-sectional area of median nerve to ulnar nerve in diagnosing carpal tunnel syndrome: a case control study - Yi-Wei Chang; Tsung-Cheng Hsieh; I-Shiang Tzeng; Valeria Chiu; Pei-Jung Huang; Yi-Shiung Horng (BMC Medical Imaging, 2019)
Abstract Background To evaluate the diagnostic accuracy of the median-to-ulnar nerve ratio (MUR) and the median-to-ulnar nerve difference (MUD) in patients with carpal tunnel syndrome (CTS). Methods In this study, 32 patients with CTS and 32 healthy volunteers were evaluated. All participants received a series of tests and ultrasound examination for the evaluation of the following criteria: cross-sectional area of the median nerve at the pisiform level (CSA-P), swelling ratio (SR), MUR, MUD, and flattening ratio (FR). Results CSA-P, SR, MUR, and MUD were all significantly larger in the patients with CTS than in the healthy volunteers. The areas under the receiver operator characteristic curves of MUD, MUR, CSA-P, and SR were 0.78, 0.75, 0.70, and 0.61 respectively. MUD had higher sensitivity (84%) than MUR, CSA-P, and SR (sensitivity: 63, 63, and 53%, respectively). Conclusions By using the ulnar nerve area at the pisiform level as an internal control parameter, the MUD and MUR methods showed higher diagnostic accuracy than SR in patients with CTS. Further application of these methods in research and clinical settings is recommended. Trial registration Clinicaltrial.gov NCT03033173. Registered 18 January 2017. Retrospectively registered.